Learn to speak Japanese, English, Filipino - Belvez, Paz M. (Rex Books Store, 2003)
A trilingual (Japanese-English-Filipino) word listing consisting of translations, basic grammar, expressions and conversations to help learners of basic Japanese, English and Filipino vocabulary to carry on simple conversations in the three languages on a self-study basis.